Unraveling sickle cell anemia with widespread lymphadenopathy - Preetham, S M; Balachandra, G; Swamy, Sumedha (Indian Journal of Case Reports, 2025)
Tuberculosis (TB) remains highly prevalent in India, with extrapulmonary forms comprising 15–20% of cases. Among these, tuberculous lymphadenitis is the most frequent manifestation. Sickle cell disease (SCD) predisposes patients to infections due to functional asplenia and impaired immune responses. The coexistence of TB and SCD presents diagnostic and therapeutic challenges. We report the case of a 25-year-old female with known SCD, status-post allogeneic hematopoietic stem cell transplant, who presented with progressive right cervical lymphadenopathy evolving over 10 months. She later developed a fever and productive cough. Clinical examination revealed multiple cervical lymph nodes and mild hepatomegaly. Imaging and biopsy confirmed necrotizing granulomatous lymphadenitis with acid–fast bacilli, establishing the diagnosis of tuberculous lymphadenitis. The patient was initiated on first-line anti-tubercular therapy with isoniazid, rifampicin, pyrazinamide, and ethambutol at standard weight-based doses. She demonstrated symptomatic improvement and regression of lymphadenopathy on follow-up. This case highlights the atypical and often indolent presentation of TB in SCD patients. The overlap of two geographically co-endemic diseases may contribute to underdiagnosis. Awareness of this association and early consideration of TB in the differential diagnosis of chronic lymphadenopathy in SCD is essential. Tuberculous lymphadenitis should be strongly suspected in immunocompromised patients with SCD presenting with persistent lymphadenopathy. Early diagnosis and treatment can prevent morbidity and misdiagnosis.